2019
DOI: 10.1042/bsr20180879
|View full text |Cite
|
Sign up to set email alerts
|

MiR-218-5p targets LHFPL3 to regulate proliferation, migration, and epithelial–mesenchymal transitions of human glioma cells

Abstract: Glioblastoma (GBM) is a main subtype of high-grade gliomas with features in progressive brain tumor. Lipoma HMGIC fusion partner-like 3 (LHFPL3) is reported to be highly expressed in malignant glioma, but the relationship and mechanism between LHFPL3 and tumor is inexplicit. The present study aimed to screen the miRNAs targeting LHFPL3 and verify the pathogenesis and development of gliomas. Bioinformatics software predicted that miR-218-5p and miR-138-5p can specifically bind to LHFPL3 mRNA. And the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Both factors belong to the "inhibitors of apoptosis proteins" family and are upregulated in uveal melanoma as well 39 . The most significantly upregulated DEG in CM was LHFPL3, which is also highly expressed in malignant glioma and can be inhibited by miRNA-218-5p thus reducing the invasiveness of glioma cells 40 . Further studies will be necessary to investigate the presented factors and signaling pathways in the development of CM in more detail and to validate them as potential therapeutic targets for the treatment of CM.…”
Section: Discussionmentioning
confidence: 99%
“…Both factors belong to the "inhibitors of apoptosis proteins" family and are upregulated in uveal melanoma as well 39 . The most significantly upregulated DEG in CM was LHFPL3, which is also highly expressed in malignant glioma and can be inhibited by miRNA-218-5p thus reducing the invasiveness of glioma cells 40 . Further studies will be necessary to investigate the presented factors and signaling pathways in the development of CM in more detail and to validate them as potential therapeutic targets for the treatment of CM.…”
Section: Discussionmentioning
confidence: 99%
“…The DSV located at chromosome 7 starts with 104,473,711 end with 104, 474,263; the length of DSV was 552 bps. The study has found that LHFPL3, the expression of miR-218-5p and miR-138-5p, was downregulated, which correlates to a reduction in cell activity, proliferation, and invasive human ability glioma cells [28]. The deletion in LHFPL3 leads to gene loss of function, which caused a worsening prognosis in colorectal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the miR-218-5p plays a key role in preventing the invasiveness of glioma cells. Zhixiao et al noticed that miR-218-5p can specifically bind to LHFPL3 mRNA and inhibit epithelial-mesenchymal transitions [ 45 ]. This is another possible reason to support these results.…”
Section: Discussionmentioning
confidence: 99%